Incidence of nosocomial pneumonia and causative bacteria among chronically ill patients admitted in a general hospital - Sangsawang, Klairoong; Luksamijarulkul, Pipat; Siri, Sukhontha; Pitikultang, Supachai (Chulalongkorn Medical Journal, 2023)
Background : Nosocomial pneumonia (NP) is ranked high among all health care associated infections. The incidence and causative bacteria may be different from studied hospital to the others. Objective : To investigate incidence of NP and its causative bacteria among chronically ill patients who were admitted at a general hospital in the central region of Thailand. Methods : A prospective study, which was carried out in department of medicine of a general hospital in the central region of Thailand from April to September 2016. A total of 330 chronically ill patients who were admitted to the department of Medicine. NP is defined as pneumonia with onset no less than 48 hours after hospital admission and NP diagnosed by doctors. The causative bacteria were cultured from sputum of NP patients. Identification was carried out by standard biochemical profile and to test the multi-drug resistance of the bacteria from the microbiological laboratory of the study hospital. The descriptive statistics were used to analyze data. Results : Among 330 chronically ill patients, 50% were female, and 58.2% were over 60 years of age. The incidence of NP was 16.4% (54/330) or 17.0 per 1,000 patient-days. The incidence of ventilator associated pneumonia (VAP) was 43.5% (40/92) or 32.7 per 1,000 ventilator days and the incidence of hospital-acquired pneumonia (HAP) was 5.9% (14/238) or 8.0 per 1,000 patient-days. Female patients, with age > 60 years, with underlying diseases such as cardiovascular and metabolic syndrome, patients with subconscious and unconscious, those with total dependence, those with long admission days, and those with medical instrument uses had relatively higher incidence of NP. The most predominant causative bacteria was A. baumannii (34.3%). Among sputum with A. baumannii, 79.2% were multiple-drug resistance A. baumannii (MDR - A. baumannii). Conclusion : Chronically ill patients admitted at the hospital, especially, those with long duration of admission and/or receiving medical instrument had relatively higher incidence of NP. Among them, the predominant causative bacteria was A. baumannii with multiple-drug resistance.